Peta Konsep Pendidikan Islam Perspektif Abuddin Nata - Ramadhani, Farah Mulya; Rachmah, Harnum Anzili; Ramadhani, Lailya Nur; Faizin, Moh. (DIKLINKO JOURNALS PUBLISHER, 2025)
This paper discusses concept maps as a learning medium in Islamic education. Concept maps function to systematically organize knowledge, helping learners understand the interrelation of core elements of Islamic education such as aqidah, worship, morality, knowledge, and da’wah. Through visualization, this method enhances motivation, comprehension, and critical thinking skills. Moreover, concept maps support the integration of religious and general knowledge, making Islamic education more relevant to contemporary needs. Despite implementation challenges, concept maps are considered effective in improving the quality of learning and shaping Muslims who are faithful, knowledgeable, and morally upright.